Correction: Bartha et al., How to measure adherence to a Mediterranean diet in dental studies: is a short adherence screener enough? : a comparative analysis : correction - Bartha, Valentin; Exner, Lea; Meyer, Anna-Lisa; Basrai, Maryam; Lüthgens, Daniela; Adolph, Michael; Bruckner, Thomas; Meller, Christian; Wölber, Johan; Wolff, Diana (Nutrients, 2022)
The authors would like to make a correction in a recently published paper [...]
Gesehen am 11.06.2022
Die originale Abhandlung wurde am 19.03.2022 veröffentlicht